Grid Computing: Software Environments and Tools - Rana, Omer F.; Cunha, Jose Cardoso (Springer London : Imprint: Springer, 2006)
With the emergence of regional, national and global programmes to establish Grid computing infrastructure, it is important to be able to utilise this infrastructure effectively. Specialist software is therefore necessary to enable the deployment of applications over such Grid infrastructure, and to help software developers construct suitable components. The uptake of Grid computing technologies will be restricted by the availability of suitable methodologies and tools. The aim of this book is to identify exemplary software engineering techniques for Grid environments, along with specialist tools that encapsulate such techniques. Case studies that illustrate their use are also discussed. The book provides: • Discussion of software engineering and modelling tools for the Grid • Analysis of issues inherent in enabling distributed computing across the Grid • Consideration of the software engineering support necessary for managing Grid applications • Proposal of a posited software engineering lifecycle to support application development for Grid Environments (along with associated tools). • Identification of novel concepts, methods and tools within Grid computing which can be put to work in the context of existing experiments and application case studies.